Application of Huygens’ Metasurfaces to the Arbitrary Design of a Leaky-Wave Antenna - Abdo-Sánchez, María Elena; Epstein, Ariel; Eleftheriades, George V. (My University, 2017)
Leaky-wave antennas are guiding structures that leak power along their length. Their radiation is mainly characterized by the propagation constant (leakage factor and phase constant) of the traveling wave. In this contribution, a leakywave antenna based on parallel-plate waveguide is proposed. Arbitrary control of the leakage factor and the phase constant is achieved by replacing the top plate by an omega-type bianisotropic Huygens’ metasurface, which implements the desired field transformation. The theoretical derivation and design methodology are briefly described. Several designs with different pointing angles (phase constants) and leakage rates have been carried out. Electromagnetic simulation results validate the theoretical derivation, highlight the capabilities of the structure and confirm the flexibility in the design parameters.
Keywords: Antenas; Metasurface; Leaky Wave Antenna; Huygens